1993
DOI: 10.1007/bf01370383
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous identification of amphetamine and its derivatives in urine using HPLC-UV

Abstract: An HPLC-UV method for the simultaneous identification of amphetamine, methamphetamine, 3,4-methylenedioxyamphetamine (MDA) and 3,4-methylenedioxymethamphetamine (MDMA) in urine is described. It includes a rapid extraction procedure of the 4 analogs from urine using Extrelut 3 columns, derivatization with sodium 1,2-naphthoquinone-4-sulphonate (NQS) to obtain highly chromophoric UV-VIS derivatives, and a final HPLC analysis using an ion-pair reversed-phase technique with eluent monitoring at 480 nm. Structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The CE-MS analysis allow the quantitative determination of amphetamine derivates comparable in sensitivity, accuracy and precision to LC-MS techniques [14,16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CE-MS analysis allow the quantitative determination of amphetamine derivates comparable in sensitivity, accuracy and precision to LC-MS techniques [14,16].…”
Section: Resultsmentioning
confidence: 99%
“…To date, the determination of amphetamines in urine samples has been mainly on GC-MS [8][9][10][11][12] and HPLC-DAD [7,[13][14]. In the last few years, the liquid chromatography coupled mass spectrometry (LC-MS) has developed rapidly in forensic and clinical applications as well as in analysis of amphetamines in biological samples [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The methods generally used water/acetonitrile mobile phases operated in gradient mode. All studies reported extraction recoveries of 85-102% for all the analytes, with LLOQs ranging from 5 to 60 ng/ml (Tedeschi et al, 1993;Falco et al, 1996;Hernandez et al, 1997;Al-Dirbashi et al, 1997;Al-Dirbashi et al, 2000;Soares et al, 2001).…”
Section: Stimulants and Alkaloidsmentioning
confidence: 97%
“…Solid-phase extraction is useful for selective extraction of target compounds from various matrices, such as biological samples or food, and has become more popular for the analysis of abused drugs [7,8]. Shimoda et al [9] successfully used a porous polymer beads column to concentrate aroma components in foods.…”
Section: Extraction Of Aroma Components From Beverages and Beverage Smentioning
confidence: 99%